(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Urinary tract infections are a serious public health problem worldwide. The development and spread of drug-resistant bacterial strains have increased the complexity of managing and treating urinary tract infections. Objective: The aim of this study was to determine the microorganisms causing urinary tract infections and their antimicrobial resistance in urinary tract infections patients admitted to Thong Nhat Hospital from April 1, 2023, to April 30, 2024. Method: cross-sectional, descriptive study. Result: Collecting 901 positive urine culture samples, the female rate (61%) was higher than male rate (39%) and mainly occurred in those over 60 years old (80%). The common bacteria causing urinary tract infections were: E. coli (54,6%); K. pneumoniae (12,1%); P. aeruginosa (6,9%); Enterococcus spp (4,6%); P. mirabilis (5,1%); E. aerogenes (3,0%). The antibiotic resistance of some isolated urinary tract infection – causing bacteria was as follows: E. coli resistance to cephalosporins ranged from 38,9% to 73,4%, with over 75% resistance to quinolones, yet it remained 100% sensitive to amikacin and over 90% sensitive beta-lactams ranged from 51,7% to 79,2%; resistance to carbapenems ranged from 21,8% to 51,1% and over 65% resistance to quinolones; the sensitivity rate to amikacin was 78,1% and to tigecycline was 100%. The antibiotic resistance rate of P. aeruginosa ranged from 50% to 67,7% with sensitivity rate of 74,2% to piperacillin/tazobactam. Enterococcus spp. had a sensitivity rate of 100% to tigecycline, 78% to teicoplanin and 75,6% to vancomycin. Conclusion: E. coli is the most common cause of urinary tract infections. Antibiotic resistance of bacteria is increasing in hospital.